ZnxCd1-xS thin films: A study towards its application as a reliable photodetector. (January 2020) - Barman, Biswajit; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: A reliable and stable photodetector shows enormous potential applications in health monitoring, intelligent wearable devices, and biological sensing. The noble opto-electrical properties of cadmium sulfide (CdS) makes it a favorable semiconductor for opto-electrical devices. The properties of CdS thin film can further be enhanced by alloying it with zinc sulfide (ZnS) to form Znx Cd1-x S compound semiconductor. Herein, a high performance, Znx Cd1-x S (x = 0, 0.15, 0.30, and 0.45) photodetector with good stability is designed and fabricated via a simple vacuum thermal evaporation technique. The various photodetector parameters of the Znx Cd1-x S films were investigated as a function of its composition. Among the various compositions of the Znx Cd1-x S thin films, the Zn0.15 Cd0.85 S films displayed excellent photosensitivity as high as 2.22 which is 1.6 times higher than that of undoped CdS thin films. The research data suggests that a high-performance single layer Znx Cd1-x S photodetector with good stability and reproducibility can be fabricated using a thermal evaporation technique. Highlights: A high performance Znx Cd1-x S (x = 0, 0.15, 0.30, and 0.45) photodetector with good stability is designed and fabricated via a simple vacuum thermal evaporation technique. The photodetector properties of the thermally deposited Znx Cd1-x S films as a function of its composition 'x' is reported for the first time to the best of our knowledge. The Zn0.15 Cd0.85 S thin films displayed excellent photosensitivity as high as 2.22 which is 1.6 times higher than that of undoped CdS thin films. Photoconductivity vs time response plots of the Znx Cd1-x S films illustrated highly reproducible photoconductivity values.